Indian potato varieties - Tiwari, Jagesh Kumar; Kumar, Vinod; Bhardwaj, Vinay; Luthra, S K; Singh, R K; Pandey, N K; Chakrabarti, S K (Indian Horticulture, 2019)
Potato is the most important non-cereal food crop of the world. It is third most staple food after rice and wheat. Potato has rich nutritive values and is wholesome food. It yields more edible energy, high protein-calorie ratio (17g protein:1000 kcal), high yield potential protein and dry matter per unit area and time compared to the cereal crops. Potato protein has a very high biological value (98) due to presence of balanced amino acids. Owing to several advantages, here we describe about the Indian potato varieties developed by ICAR-Central Potato Research Institute, Shimla, Himachal Pradesh for cultivation in the different parts of the country.